High school and higher education in Colombia seen from the Saber tests perspective (2019)
Standardized testing generates debate when it comes to assessing the quality of education. However, it constitutes a tool for characterization of students. Colombia seems to be the only country in the world where it is possible to monitor a student’s high school and university standardized tests performance. This study aims to characterize the students who took both tests. Contingency tables in Excel were created using data from students in Colombia who finished high school and earned a bachelor’s degree; those who took the Saber 11 test between 2005 and 2006 and, 4 or 5 years afterwards, they took the Saber Pro test in institutes of a technical and university nature or just universities. 6 out of 10 students who finished their higher education studies attended private high schools or private universities. Approximately 2 out of 3 students finish their higher education studies at a university. Significant differences by gender exist in the Saber 11 test, which are correlated with the Saber Pro test. Public universities have higher Saber Pro scores than private universities.